226k views
3 votes
Solve the following equations.
ln(x + 1) − ln(2) = 1

1 Answer

2 votes

Answer:

The sollution is x = 2e -1

Explanation:

Hi there!!

First, let´s write the equation:

ln(x + 1) - ln(2) = 1

Apply logarithm property: ln(x+1) - ln(2) = ln((x+1)/2)

ln((x+1)/2) = 1

Apply e to both sides of the equation

e^[ln((x+1)/2)] = e¹

Apply e^[ln((x+1)/2)] = (x+1)/2

(x + 1) / 2 = e

Multiply by 2 both sides of the equation

x + 1 = 2e

Substract 1 from both sides of the equation

x = 2e - 1

The sollution is x = 2e -1

Have a nice day!

User Nikk Wong
by
5.3k points